2013
DOI: 10.3788/col201311.021102
|View full text |Cite
|
Sign up to set email alerts
|

Improved illumination for vision-based defect inspection of highly reflective metal surface

Abstract: Specular and strong reflections are the main problems encountered during part image defect inspection of shiny or highly reflective surfaces. In this letter, we propose an improved illumination method for defect inspection. A diffuse light source is designed based on the physics analysis of light reflection. The distribution of intensity is simulated according to a known model to verify the illumination uniformity of the source. Experiments show that defect expressivity when using the proposed illumination met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The basic concept of INMI-based methods [21][22][23][24][25][26][27][28][29][66][67][68] is to obtain images of the real measured workpieces, which can be represented in the form of grayscale images through visual detection under the SL system to complete the image acquisition of the measured workpieces.…”
Section: Inmi Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic concept of INMI-based methods [21][22][23][24][25][26][27][28][29][66][67][68] is to obtain images of the real measured workpieces, which can be represented in the form of grayscale images through visual detection under the SL system to complete the image acquisition of the measured workpieces.…”
Section: Inmi Methodsmentioning
confidence: 99%
“…Quan et al designed an array pattern hole template, which can realize the batch feeding, rolling and detection of steel balls, and cooperates with SL equipment to solve the problems of the reflection of the polished surface of steel balls and the mutual projection between them [25]. Li et al designed a circular diffuse dome light source based on LEDs [26]. To eliminate the shadows formed by surrounding objects and reflect bright spots, a circular LED array was designed that had a dome-shaped diffuse reflection wall above the circular LED array.…”
Section: Inmi Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The segmentation object in this paper is a magnesium ingot with a trapezoidal cross-section, and the specific dimensions are shown in Figure 1 a. The surface of the target magnesium ingot is smooth and local overexposure will occur in the acquired image under a complex external light environment [ 8 ]. When the image is segmented, the gradient of partial gray value information of the magnesium ingot changes dramatically, and the segmentation result of the magnesium ingot obtained by traditional methods is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can only be applied for sampling checks, but not for 100% checks. Li et al [8] presented an improved optical illumination model. Experiment results showed that the designed illumination system has higher defect expressivity.…”
Section: Introductionmentioning
confidence: 99%